Peranan Majlis Agama Islam Negeri Johor semasa Perintah Kawalan Pergerakan (PKP) akibat Pandemik COVID-19 - Zainol, Nur Zainatul Nadra; Abd Khalim, Mustapahayuddin; Wan Zahari, Wan Ainaa Mardhiah; Abdullah, Azlan Kuangit (2021)
The Johor State Islamic Religious Council (MAIJ) was established on 1925 under the authority of Part IV, Chapter XV, Board of Regulations for the Rule of the King. There are initial functions and main functions for MAIJ. MAIJ's initial function was to manage religious affairs, provide advice on the King's customs, provide lessons / education to the King's relatives and manage the welfare of the Muslim community. Meanwhile, its main function is to manage and administer the Group of Zakat & Fitrah Fund (Kumpulan Wang Zakat & Fitrah) and distribute the fund according to asnaf, manage and administer the Fund / Baitulmal Property and the Wakaf Fund as a Wakaf Trustee. This article aims to analyze the types of assistance and contributions due to Covid-19 pandemic during the Movement Control Order (MCO) on 18 March 2020 to 31 March 2020 organized by the Johor Islamic Religious Council. This study is a qualitative study with content analysis design. The results show that the Johor Islamic Religious Council provides assistance to people in need with a set amount along with the number of recipients to be in line with the budget. This study lists the types of donations along with the amount of aid money as a reference for recipients during the period of the Movement Control Order (MCO)